Development of Resources and Integration of Spiritual Values: A Model for the Development of State Apparatuses in Situbondo District - Nina Sa’idah Fitriyah; Arief Tukiman Hendrawijaya; Selfi Budi Helpiastuti; Edy Wahyudi (Journal of Social Interactions and Humanities, 2023)
This article discusses the development of human resources and the integration of spiritual values in the context of developing state apparatus in Situbondo Regency. Human resource development is not only related to increasing technical competence but also involves aspects of values and spirituality. Spiritual values include integrity, ethics, morality, responsibility, values-based leadership, and concern for the welfare of society. The integration of spiritual values aims to create responsible, fair, and public service-oriented officials. The results of this study show that a model for developing state apparatus that integrates spiritual values is a strong foundation in increasing technical competence and forming good character. The Situbondo Regency Government took steps which included identifying and introducing spiritual values, training and developing ethics, fostering values-based leadership, integrating spiritual values into organizational policies and processes, and improving welfare and work balance. Through this approach, it is hoped that state apparatus in Situbondo Regency will be created who are not only competent in the technical field but also have a good attitude and respect moral values. The development of human resources with a spiritual approach will help create public services that are of high quality, transparent, and oriented to the interests of the community.